Regulating Consensual Sexual Behaviour between Older Children: The Case against the Current Approach under the Sexual Offences (Scotland) Act 2009. Issue 2 (May 2019) - Callander, Isla
Abstract : The purpose of this article is to critically examine the current approach to regulating the consensual sexual behaviour of older children in Scots law. At present, blanket criminalisation applies to all consensual sexual intercourse and oro-genital sexual activity between two older children, defined by statute as those aged 13 to 15, through specific offences under section 37 of the Sexual Offences (Scotland) Act 2009. The first part of this article will describe the nature of, and background to, section 37. This will then be contextualised against the evidence of the relatively widespread occurrence of sexual intercourse amongst older children, and the very limited number of prosecutions under the provision in practice. While acknowledging that there are clear reasons to encourage older children to delay their first sexual experiences, the second part of the article will use an inter-disciplinary approach to show the extent to which the current criminal law approach is genuinely problematic. This is in terms of its conformity to rule of law principles, possible adverse social consequences and potential ineffectiveness. The final part of the article will conclude that the current approach in Scotland is wholly inappropriate, and that a more appropriate approach would be for Scots law to move towards a revised section 37 offence which incorporates an element of exploitation which the prosecution should have to prove.